FORMS OF VIOLENCE REFERRED TO SCHOOL EVERYDAY IN THE VIEW OF A PUBLIC SCHOOL TEACHERS - Mariana Aparecida Costa; Rayssa Nogueira Rodrigues; Luciana Netto; Jaqueline dos Santos; Gabriel Alves Tatagiba (Universidade Federal de Santa Maria, 2013)
http://dx.doi.org/10.5902/217976927605 Aim: to comprehend the forms of violence referred to in school life from the perspective of teachers. Method: this is a qualitative study with semi-structured interview conducted from September 2010 to October 2011, conducted with nine public school teachers of a municipality in the Midwestern region of Minas Gerais. Data were analyzed by content analysis. Results: the speech of teachers resulted in the categories: the daily contact with psychological violence, the meaning of physical violence and violence against property as a form of protest and reaffirmation while subject. Conclusions: this study shows that school environment is affected by many problems, among them various forms of violence. In the meantime, it is imperative to perform preventive interventions stamp from creative actions and inclusive with participation and support of the school community, parents and society, with emphasis on the role of professional services and health promotion.